Dance as text : ideologies of the baroque body - Franko, Mark (RES monographs in anthropology and aesthetics., 1993)
Dance as Text: Ideologies of the Baroque Body is a historical and theoretical examination of French court ballet over a hundred-year period, beginning in 1573, that spans the late Renaissance and the early baroque. Utilizing aesthetic and ideological criteria, Mark Franko analyzes court ballet librettos, contemporary performance theory, and related commentary on dance and movement in the literature of this period. Examining the formal choreographic apparatus that characterizes late Valois and early Bourbon ballet spectacle, Franko postulates that the evolving aesthetic ultimately reflected the political situation of the noble class, which devised and performed court ballets. He shows how the body emerged from verbal theater as a self-sufficient text whose autonomy had varied ideological connotations, most important among which was the expression of noble resistance to the increasingly absolutist monarchy.